Agents of War: A History of Chemical and Biological Weapons, Second Expanded Edition - Spiers, Edward M. (Reaktion Books, Limited, 2021)
Cover -- Title Page -- Copyright Page -- Contents -- Preface -- Abbreviations -- Introduction -- 1. The Legacy of Gas Warfare in the First World War -- 2. Deterrence and Disarmament: Responses to Chemical and Biological Warfare, 1919-93 -- 3. Chemical Warfare in Third World Conflicts -- 4. The Proliferation of Chemical and Biological Weapons -- 5. Iraq's Chemical and Biological Warfare Programmes -- 6. Chemical and Biological Terrorism -- 7. The Recurrence of Chemical Warfare in the Middle East -- 8. Political Assassination by Poisoning -- Conclusion: The Evolving Nature of Chemical and Biological Warfare -- References -- Select Bibliography -- Acknowledgements -- Index.